Efektivitas Komunikasi Organisasi dalam Kaitannya dengan Optimalisasi Fungsi Subak (Kasus di Subak Munggu, Desa Cempaga, Kabupaten Bangli) - WIJAYANTI, PUTU UDAYANI; SUSRUSA, KETUT BUDI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
The Effectiveness Of Organizational Communication In Its Relations By Optimizing The Subak Function (Case In Subak Munggu, Cempaga Village, Bangli District). Agriculture in Bali is closely related to the existence of Subak which has been known since 1071 AD as one of the three main pillars supporting Bali's fame. Subak is a Balinese cultural heritage which plays a very important role in the development of agricultural development in Bali, by applying the Tri Hita Karana (THK) philosophy, the three causes of happiness, namely the existence of a harmonious relationship between humans and God, humans and fellow humans, and humans and nature. Subak is declared as a farmer-based irrigation system and an independent institution (self-governed irrigation institution). Based on Bali Province Regional Regulation No. 9 of 2012, Subak is a traditional organization of indigenous communities in Bali in the field of water and plant use that is socio-agrarian, religious and economic at the farming level. According to Windia (2010), daily Subak activities include spiritual activities related to various religious ceremonies, mutual cooperation activities of Subak organizations regulated in customary regulations (awig-awig), management of irrigation systems with a proportional concept, regarding lending water to each other. , and others. These subak activities or activities are related to the five functions of subak as an irrigation system, namely (1) carrying out religious ceremonies, (2) sharing and distributing irrigation water, (3) management or mobilization of farmer resources, (4) maintenance of irrigation canals, and ( 5) conflict handling or management.